Исследования влажности древесно-полимерных материалов на основе вторичных полимеров - Лебедев, Владимир Владимирович; Карев, Артем Игоревич; Чавров, Сергей Александрович (НТУ "ХПИ", 2012)
Проведены исследования влажности древесно-полимерных композитов на основе отходов полипропилена и органических отходов и ее влияние на технологические характеристики образцов.

Researches of humidity of wood and polymeric composites on the basis of a waste of polypropylene and an organic waste and its influence on technical characteristics on samples are carried out.
Rheological researches of pollution-free wood-polymeric materials on the basis of a waste of polypropylene and an organic waste
Keywords: отходы; полипропилен; композиты; переработка; processing; polymers; wood; humidity; waste